A comparative study on flank wear of ceramic and Tungsten carbide inserts during high speed machining of stainless steel - Khan, Ahsan Ali; Mohiuddin, A. K. M.; Norhamzan, Norainnatul Husna (Research India Publications, 2018)
To meet the challenge of higher speeds for higher production rates, carbides (also known as cemented or sintered carbides)were introduced in the 1930s. Tungsten carbide (WC) is a composite material consisting of tungsten-carbide particles bonded together in a cobalt matrix; an alternate name for WC is cemented carbides. As the cobalt content increases, the strength, hardness, and wear resistance of WC decrease, while its toughness increases because of the higher toughness of cobalt. Alumina based ceramic tools consist primarily of finegrained, high-purity aluminum oxide. They are cold-pressed into insert shapes under high pressure and sintered at high temperature. Additions of titanium nitride and zirconium oxide help improve properties such as toughness and thermalshock resistance. However, ceramics are very brittle, and their use may result in premature tool failure by chipping of the cutting edges or catastrophic failure. Due to their brittleness they are effective in high-speed, uninterrupted cutting operations. Because of their high hardness over a wide range of temperatures, high elastic modulus and thermal conductivity, and low thermal expansion, carbides are among the most important, versatile, and cost-effective tool and die materials for a wide range of applications. In the present research work a study has been done to compare the flank wear of ceramic and tungsten carbide inserts during high speed machining. As flank wear increases, friction between the tool and the workpiece also increases. This results poor work surface finish and increase in cutting force and consequently more flank wear. It was found that for both ceramic and tungsten carbide tools flank wear increases with increase in cutting speed, feed rate and depth of cut. But cutting speed is the most significant factor resulting flank wear. The results of the investigation shows that flank wear is more for ceramic tools compared to that of carbide tools for most of the experiment runs. The reason behind it is, with increase in cutting parameters like cutting speed, feed rate and depth of cut, vibration during machining increases that results microchipping of the cutting edge resulting higher flank wear. But when the cutting parameters are low, then less vibration occurs and ceramic tools shows better performance than carbides in terms of flank wear.